Hausa Calligraphic and Decorative Traditions of Northern Nigeria: From the Sacred to the Social - Kurfi, Mustapha Hashim (Islamic Africa, 2017)
In the past, sacred Islamic calligraphies were used strictly in sacred places, whereas profane calligraphies were used in secular spheres. However, the trend now among some Hausa artists is to extend the sacred Islamic calligraphic tradition to the social domain. Some Hausa calligraphers do so by “desacralizing” their Islamic-inspired calligraphies. This article deals with the extension of Islamic decorations to secular social domains in Kano, Northern Nigeria. Such works are produced by calligraphers like Sharu Mustapha Gabari. I show how Hausa calligraphers like Mustapha Gabari creatively extend their arts, talents, and skills to other social domains. These domains include the human body, clothing, houses, and other objects. This article describes the ways in which the sacred and the secular realms overlap, and illustrates some key processes of enrichment the Islamic arts have undergone in sub-Saharan Africa. These processes exemplify the ʿAjamization of Islamic arts in Africa, especially how sub-Saharan African Muslims continue to creatively appropriate and enrich the Islamic calligraphic and decorative traditions to fit their local realities and address their preoccupations.